2019
DOI: 10.3390/insects10100360
|View full text |Cite
|
Sign up to set email alerts
|

Insecticidal Activity of Compounds of Plant Origin on Mahanarva spectabilis (Hemiptera: Cercopidae)

Abstract: The damage caused by spittlebugs varies according to the species of grass, and the losses can reach alarming levels. Measures for population control are currently restricted to the use of resistant grasses and the diversification of pastures. Therefore, alternative control measures are necessary, such as the use of botanical insecticides. The aim of this study was to evaluate the insecticidal activities of thymol, carvacrol, eugenol, cinnamaldehyde, and trans-anethole on Mahanarva spectabilis eggs, nymphs, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 51 publications
0
18
0
Order By: Relevance
“…Imidacloprid, the first commercialized insecticide of this class with high effectiveness against several sucking pests ( Tomizawa and Casida, 2003 ; Lu et al, 2016 ), and it has been used as a seed treatment for controlling grain aphids in recent years ( Miao et al, 2014 ). However, concerning the environmental impacts and resistance, the application of botanical insecticides such as abamectin, matrine and rotenone has been augmented ( Dias et al, 2019 ; Jesser et al, 2020 ). New types of insecticides provide more choices for pest management, but the effectiveness needs further studies.…”
Section: Introductionmentioning
confidence: 99%
“…Imidacloprid, the first commercialized insecticide of this class with high effectiveness against several sucking pests ( Tomizawa and Casida, 2003 ; Lu et al, 2016 ), and it has been used as a seed treatment for controlling grain aphids in recent years ( Miao et al, 2014 ). However, concerning the environmental impacts and resistance, the application of botanical insecticides such as abamectin, matrine and rotenone has been augmented ( Dias et al, 2019 ; Jesser et al, 2020 ). New types of insecticides provide more choices for pest management, but the effectiveness needs further studies.…”
Section: Introductionmentioning
confidence: 99%
“…Several methods including the use of synthetic chemical insecticides and biopesticides have been used to control this pest [ 6 ]. However, the foaming substance produced by the spittlebug nymphs, which protects them against predators and parasitoids and acts as thermal insulation [ 9 ], is an important obstacle in their management [ 10 ]. Indeed, the chemical composition of and beneficial organisms contained in the foam produced by spittlebugs protect the nymphs [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Park et al ( 2017 ) measured the insecticidal activity of thymol, carvacrol, citral, 2-isopropylphenol, 3-isopropylphenol, and 4-isopropylphenol against Pochazia shantungensis adults, and their LC 50 values were 28.52, 56.74, 89.12, 71.41, 82.49, and 111.28 mg/L, respectively. Dias et al ( 2019 ) evaluated the toxicity of thymol, cinnamaldehyde, carvacrol, eugenol, and trans-anethole on Mahanarva spectabilis eggs, nymphs, and adults, and they found that treatments with eugenol, carvacrol, and thymol showed the highest mortalities, presenting efficiencies higher than 85% after 48 h of application. Traboulsi et al ( 2002 ) found that the compounds thymol, carvacrol, (1R)-(+)-α-pinene, and (1S)-(–)-α-pinene showed potent toxicity (LC 50 36–49 mg/L), whereas menthone, 1,8-cineole, linalool, and terpineol (LC 50 156–194 mg/L) were less toxic to the mosquito Culex pipiens molestus.…”
Section: Discussionmentioning
confidence: 99%